Evaluating Water Characteristics and Their Effects on Reducing Water pH Using Citric Acid - Maxwell L. Corso; Jason C. Woodworth; Mike D. Tokach; Jordan T. Gebhardt; Joel M. DeRouchey; Robert D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 45 water samples from swine production sites across six states were analyzed to determine the effects of water characteristics on reducing water pH with citric acid. Water characteristics analyzed included hardness, pH, calcium (Ca), and magnesium (Mg). Total hardness was calculated as the combined values of Ca and Mg and expressed as mg of CaCO3/L. Water hardness ranged from 142 to 1,181 mg CaCO3/L with an average of 441.2 mg CaCO3/L. Initial sample pH ranged from 7.42 to 8.47 with an average value of 7.91. In triplicate, 10 mL of water from each source was titrated with citric acid to reach a stable pH of 5.0, 4.5, and 4.0 ± 0.05. An inverse relationship between sample hardness and initial pH was observed (quadratic, P = 0.002; R2 = 0.22). The amount of citric acid required to reach a sample pH of 4.0 increased (quadratic, P < 0.001) as hardness, Ca, and Mg increased (R2 = 0.30, 0.27, 0.28, respectively). Unexpectedly, high initial sample pH was associated with a reduction (quadratic, P < 0.001; R2 = 0.31) in the amount of citric acid required to reach a pH of 4.0. In conclusion, water hardness, Ca, Mg, and initial pH cannot fully predict the amount of citric acid required to reach a stable sample pH of 4.0. However, relationships were observed that can partially explain the variation in the amount of acid required. Although these relationships cannot fully determine the amount of acid required to reach the target pH, titrating to a target pH of 5.0 can predict the amount of acid required to reach a pH of 4.0 (linear, P < 0.001; R2 = 0.99). This data suggests that acid titrations of each water source should be completed to determine the amount of acid required to reach a final water pH of 4.0.
Keywords: calcium; hardness; magnesium; pH